Magnitude of neonatal asphyxia and its predictors among newborns at public hospitals of Wolaita Zone in Southern Ethiopia, 2023 - Shewazerf Gizachew; Girma Wogie; Mekasha Getnet; Arega Abebe Lonsako (BMC, 2024)
Abstract Background Neonatal asphyxia is one of preventable causes of neonatal mortality throughout the world. It could be improved by early detection and control of the underlying causes. However, there was lack of evidence on it in the study setting. Thus, the aim of this study was to assess the magnitude and predictors of neonatal asphyxia among newborns at public hospitals of Wolaita Zone in Southern Ethiopia. Method A facility-based cross-sectional study was done among 330 mothers with neonates in selected public hospitals. A systematic random sampling technique was used to select the study participants. Data were collected through an interviewer-administered questionnaire and checklist. The collected data were entered into EpiData version 4.6 and exported to SPSS version 26 for analysis. Logistic regression was fitted to examine the association between explanatory variables and outcome variable. In multivariable logistic regression, AOR with 95% CI was reported, and p < 0.05 was used to declare statistically significant variables. Results The magnitude of neonatal asphyxia was 26.4% with 95% CI: (21.8, 30.9). In multivariable logistic regression analysis primiparity (AOR = 2.63 95%CI 1.47, 4.72), low-birth-weight (AOR = 3.45 95%CI 1.33, 8.91), preterm birth (AOR = 3.58 95%CI 1.29, 9.92), and premature rupture of membranes (AOR = 5.19 95%CI 2.03, 13.26) were factors significantly associated with neonatal asphyxia. Conclusions In this study, the magnitude of neonatal asphyxia was high. From the factors, premature rapture of the membrane, parity, birth weight of the newborn, and gestational age at birth were significantly associated with neonatal asphyxia. Attention should be given to early detection and prevention of neonatal asphyxia from complicated labor and delivery.